A SYSTEMATIC LITERATURE REVIEW; PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PERUSAHAAN - Fanti Nurul Zaqiyah; Tasya Nailatal Istiqomah; Nur Fadillah; Prasetyo Hafid Mardianto; Riyan Sisiawan Putra (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
Abstract Employees are the most important asset in the company. If a company does not have employees, all operational activities of the company will not run. Employees need compensation such as bonuses, benefits, work environment, and work that can demonstrate ability, so that employees' abilities can provide their best performance to the company. Compensation and employee performance are two things that are interconnected. Where the more compensation an employee receives, either directly or indirectly, the better the employee's performance at work. So you could say that compensation and performance have a directly proportional relationship. The purpose of this study was to determine the effect of compensation and motivation on the performance of company employees. The method used in this study is Systematic Literature Review, where compensation and motivation are the x variable while the performance is the y variable. All articles used for reference in this journal are sourced from Emerald and Google Scholar, with publication times in the last 5 years. Based on the results of this study it can be concluded that there is an influence between compensation and motivation on employee performance, because with compensation and motivation employees will feel more active and enthusiastic, which will have an impact on improving company performance Keywords: Compensation, Motivation, Employee Performance